2023
DOI: 10.1177/19458924231179615
|View full text |Cite
|
Sign up to set email alerts
|

The Tissue Lymphocyte-to-Eosinophil Ratio Predicted Long-Term Recurrence of Eosinophilic CRSwNP

Abstract: Background Eosinophilic chronic rhinosinusitis with nasal polyps (Eos-CRSwNP) remains a recalcitrant disease with a high recurrence rate. Objective This study aimed to identify a predictor of long-term recurrence in patients with Eos-CRSwNP. Methods A total of 39 Eos-CRSwNP patients who had their initial and recurrent nasal polyps surgically removed were retrospectively included in this study, with 49 Eos-CRSwNP patients without recurrence and 32 patients with non-Eos-CRSwNP matched by randomly chosen. Clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Its diagnosis primarily relies on pathological tissue section examination and eosinophil count, which is invasive and subject to certain subjectivity. 34 , 35 Although previous studies have identified several potential biomarkers for predicting eCRSwNP, such as serum metabolomics, 36 nasal microbiota, 37 and the peripheral blood lymphocyte-to-eosinophil ratio, 38 their sensitivity and specificity remain relatively constrained, hindering their adoption in clinical settings. Therefore, the exploration of objective biomarkers for eCRSwNP is still a current research focus, which will contribute to achieving personalized precision treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Its diagnosis primarily relies on pathological tissue section examination and eosinophil count, which is invasive and subject to certain subjectivity. 34 , 35 Although previous studies have identified several potential biomarkers for predicting eCRSwNP, such as serum metabolomics, 36 nasal microbiota, 37 and the peripheral blood lymphocyte-to-eosinophil ratio, 38 their sensitivity and specificity remain relatively constrained, hindering their adoption in clinical settings. Therefore, the exploration of objective biomarkers for eCRSwNP is still a current research focus, which will contribute to achieving personalized precision treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al identified that a lower ratio tissue lymphocytes to eosinophils predicts recurrence within 5 years after surgery, which may help identify those who warrant more aggressive medical management. 5 Moreover, patients who undergo transplantation may be at particular risk for recalcitrant sinus disease requiring surgery. Retrospective analysis of patients chronic rhinosinusitis (CRS) with both solid and nonsolid organ transplants found an increased need for surgery and more recalcitrant disease.…”
mentioning
confidence: 99%